Transition Action Details (Tad) Strategy in Teaching Writing Recount Text - Siti Yulianti; Dwi Andriani; Zulaikah Zulaikah (Channing : Journal of English Language Education and Literature, 2020)
This thesis is entitled "The Use of Transition Action Details Strategy in Teaching Writing Ability to the Eighth Grade Students of SMP Muhammadiyah 1 Rawabening". The objective of this study was to know whether or not there are any significant differences between the student who are taught by using the Transition Action Details Strategy and the student who is not taught by using it. This study used an experimental method, a quasi-experimental design. The population of this study was 47 students, and the sample was 47 students was taken by using purposive sampling, those were 24 students of the experimental group and 23 students of the control group. Based on the calculation by using an independent t-test by using SPSS 16, The writer found that t-obtained was higher than t-table (2.868>2.014) at the significant level a=0.05 in two-tailed testing. It meant that there were any significant differences between the experimental group and the control group. So, the null hypothesis (Ho) was rejected and alternative hypotheses (Ha) were accepted. It can be concluded that Transition Actions Details Strategy was significant in teaching writing ability to the eighth-grade students of SMP Muhammadiyah 1 Rawabening.